Mystery of Divine Stories - Ahmadovich, Hayitov Shavkat (Researchparks Publishing, 2023)
The article describes Alisher Navoi's attitude to theology, the ability to use Quranic stories and symbols in the interpretation of artistic ideas. It is proven that the moral-educational, spiritual-enlightenment views of the great thinker, who relied on the truth of the divine stories, found deep expression in the artistic text. The qualities of perfection expressed in